Analysis of School Principal Leadership and Teacher Competence on Teacher Performance with Work Motivation as a Mediating Variable at SMP Negeri 1 Bandar, Bener Meriah Regency - Putri Arisa; Muhammad Toyib Daulay; Sri Rahayu (CV. Doki Course and Training, 2026)
This study aims to analyze the influence of principal leadership and teacher competence on teacher performance with work motivation as a mediating variable at SMP Negeri 1 Bandar, Bener Meriah Regency. This study uses a quantitative approach with a survey method. The study population consisted of all 74 teachers at SMP Negeri 1 Bandar, Bener Meriah Regency, all of whom were included in the study sample. Data were collected through questionnaires and analyzed using Partial Least Square (PLS) with the help of the SmartPLS application. The results showed that principal leadership and teacher competence had a positive and significant effect on teacher performance. In addition, principal leadership and teacher competence also had a positive and significant effect on work motivation. Work motivation was found to have a positive and significant effect on teacher performance. The results of the indirect effect test showed that work motivation was able to mediate the effect of principal leadership and teacher competence on teacher performance. These findings indicate that good leadership and competence will be more effective in improving teacher performance when accompanied by high work motivation. Based on the research results, it is recommended that schools improve the effectiveness of principal leadership through clearer communication of the school's vision and goals, strengthen teacher competence through continuous professional development, and increase teacher work motivation so that teacher performance can be optimally and sustainably improved.